Pemetaan Spesies Kelelawar Berdasarkan Pola Pemilihan Sarang di Gua Gale-gale Bangkang dan Gua Raksasa Tanjung Ringgit - Sucika Armiani; Siti Rabiatul Fajri (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to determine the pattern of nest selection in bat species inhabiting the Bangkang Gale-gale Cave in Prabu Village, Pujut District, Central Lombok Regency, and Tanjung Ringgit Giant Cave in Sekaroh Village, Jerowaru District, East Lombok Regency. Nests are an important component of bat life. Most types of bats live in colonies in nesting and foraging for food. This research method is descriptive exploratory by mapping cave zones, making squares, analyzing the richness and abundance of bat species at each bat nesting site. The results showed that the nest selection pattern in Gale-gale Cave, namely: Rhinolopus acuminatus, Rhinopoma microphylum, and Rhinolopus simplex were in the same group in zone / zone I. Whereas Chaerephon plicata could be found inhabiting zone / zone II, and Hipposideros ater. saevus inhabit zone / zone III. The pattern of nest selection in the Giant Cave Tanjung Ringgit, Macroglossus minimus and Eonycteris spelaea was found in both zone zone II and zone III caves. Hipposideros ater saevus and Hipposideros diadema are in the same group, namely on the border between zone II and zone III, namely the left and right sides of zone III, or not far from the water source in the cave ± 2 m above the water source, and Rosettusa amplxicaudatus inhabit zone / zone III Giant Cave Tanjung Ringgit.